Analysis on effectiveness of training evaluation system : a proposal for Sedcovest Holdings Sdn Bhd / Diana @ Dymphana Stephen Tuning, Faridah Lingam and Susie @ Suzie Stephen Tunning - Stephen Tuning, Diana @ Dymphana; Lingam, Faridah; Stephen Tunning, Susie @ Suzie (2012)
The purpose of this study is to analyse the current Training Evaluation System (TES), the tools being used and problems that are faced by one of the local government agencies, namely SEDCOVEST Holdings Sdn Bhd (SVH). This study also seeks to find out the level of effectiveness of TES in SVH. Furthermore, this study attempts to examine a more comprehensive and appropriate TES for SVH. This study uses primary data such as interview, discussion and observation as well as secondary data from published and printed information such as brochures, printed journals and articles from websites, reports and books. The findings reveal that there is a lack of effectiveness and appropriateness in SVH's TES in the area of selection of participants and evaluation approach. Another issue is on the accountability of SVH to the fund provider. While ICT is greatly used in this era, SVH employs a minimal level of technological supports in its TES. As a conclusion, the result shows that there is a need to apply an effective TES to ensure that training programmes conducted meet the vision, mission and objectives of SVH.